2020
DOI: 10.1001/jamanetworkopen.2020.13431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Opioid Prescribing Patterns in a Large Network of US Community Health Centers, 2009 to 2018

Abstract: IMPORTANCE Understanding opioid prescribing patterns in community health centers (CHCs) that disproportionately serve low-income patients may help to guide strategies to reduce opioidrelated harms. OBJECTIVE To assess opioid prescribing patterns between January 1, 2009, and December 31, 2018, in a network of safety-net clinics serving high-risk patients. DESIGN, SETTING, AND PARTICIPANTS Cross-sectional study of 3 227 459 opioid prescriptions abstracted from the electronic health records of 2 129 097 unique pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Opioid use at initiation has been shown to affect downstream consequences such as long-term use [ 22 ] and unintentional overdoses, underscoring the importance of commencing on low potency and dose on first prescription. Recent studies beyond 2015 have demonstrated a decline or a plateauing of opioid prescribing across a number of jurisdictions, especially of high-dose use and of high-strength opioids such as oxycodone [ 22 , 41 , 42 ]. In all populations, the decline in such prescribing reflects national, regulatory, federal, statewide, and local efforts, especially as portrayals related to opioid-related harms become more prevalent via the media.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid use at initiation has been shown to affect downstream consequences such as long-term use [ 22 ] and unintentional overdoses, underscoring the importance of commencing on low potency and dose on first prescription. Recent studies beyond 2015 have demonstrated a decline or a plateauing of opioid prescribing across a number of jurisdictions, especially of high-dose use and of high-strength opioids such as oxycodone [ 22 , 41 , 42 ]. In all populations, the decline in such prescribing reflects national, regulatory, federal, statewide, and local efforts, especially as portrayals related to opioid-related harms become more prevalent via the media.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic opioid use : patients who, within calendar quarter, were prescribed ≥160 opioid pills (short- or long-acting), ≥90 long-acting pills, or any methadone pills or fentanyl patches. 9 …”
Section: Methodsmentioning
confidence: 99%
“…High-dose use : chronic users who averaged more than 90 morphine milligram equivalents (MMEs) per day through any quarter in 2018. 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid use at initiation has been shown to affect downstream consequences such as longterm use [22] and unintentional overdoses, underscoring the importance of commencing on low potency and dose on first prescription. Recent studies beyond 2015 have demonstrated a decline or a plateauing of opioid prescribing across a number of jurisdictions, especially of high-dose use and of high-strength opioids such as oxycodone [22,41,42]. In all populations, the decline in such prescribing reflects national, regulatory, federal, statewide, and local efforts, especially as portrayals related to opioid-related harms become more prevalent via the media.…”
Section: Plos Medicinementioning
confidence: 99%